A tale of government spending efficiency and trust in the state - Afonso, António (2022)
This paper empirically links the efficiency and performance assessment of the general government, proxied by efficiency scores, to the trust in government. Government spending efficiency scores are first computed via data envelopment analysis (DEA). Then, relying on panel data and instrumental variable approaches, we estimate the effect of public sector efficiency on citizens trust on national governments. The sample covers 36 OECD countries between 2007 and 2019. We find that the more efficient countries in terms of government spending are Australia, Chile, Ireland, New Zealand, South Korea, Switzerland. Secondly, our main finding is that better public sector spending efficiency is positively associated with citizens’ higher trust in governments. In general, political economy variables and the existence of fiscal rules do not seem to significantly affect our measure of trust. Results were held using alternative proxies for public sector efficiency, specifications with different control variables and instrumental variables approaches.